Is Continuous Flow Superior to Pulsatile Flow in Single Ventricle Mechanical Support? Results from a Large Animal Pilot Study. Issue 4 (July 2015) - Fujii, Yasuhiro; Ferro, Giuseppe; Kagawa, Hiroshi; Centola, Luca; Zhu, Liqun; Ferrier, William T.; Talken, Linda; Riemer, R. Kirk; Maeda, Katsuhide; Nasirov, Teimour; Hodges, Bill; Amirriazi, Saleh; et al.
Abstract : Durable mechanical support in situations of physiologic single ventricle has been met with little success so far, particularly in small children. We created an animal model to investigate whether pulsatile or continuous flow would be superior. Three 1 month old sheep (10–16 kg) were instrumented. Via sternotomy and with cardiopulmonary bypass, a large ventricular septal defect and atrial septal defect were created. The left ventricle was cannulated using a Berlin Heart inflow cannula. This was connected sequentially to a continuous flow device (Thoratec HeartMate X, Pleasanton, CA) and to a pulsatile device (Berlin Heart Excor, The Woodlands, TX). Outflow was via a Y-graft to both aorta and pulmonary artery, striving for equal flow to both. Atrial filling pressures were controlled with volume infusions over a wide range. Under comparable loading conditions, significantly higher maximum flow was obtained by HeartMate X than by Excor (4.95 ± 1.27 L/min [range, 3.84–6.34 L/min] for HeartMate X vs. 1.80 ± 0.85 L/min [range, 1.01–2.7 L/min] for Excor; p < 0.05). Judging from this limited animal study, in single ventricle scenarios, continuous flow devices may achieve higher pump flows than pulsatile devices when provided with similar filling pressures. Their clinical use should be investigated. More extensive experimental studies are needed.